1977
DOI: 10.1111/j.1095-8649.1977.tb04097.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heavy metals on development of the killifish, Fundulus heteroclitus

Abstract: When F. heteroclitus embryos were exposed to inorganic mercury at concentrations of 0.03 or 0.1 mg/l at the early blastula stage, the percentage of successful axis formation was reduced and a significant proportion of embryos developed cyclopia or intermediate conditions leading to cyclopia. Treatment at the late blastula stage reduced the severity of the defects. Embryos which developed in lead at concentrations of 1 and 10 mg/l were normal in appearance until hatching, at which time they exhibited lordosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Sharp and Neff (1980) also found a reduction in hatching success in Fundulus at 10 lg HgCl 2 /l. Weis and Weis (1977) noted that 100 lg/l HgCl 2 killed all Fundulus embryos prior to the onset of gastrulation. While Samson and Shenker (2000) found that early zebrafish (Danio rerio) embryos were most susceptible to MeHg toxicity, with highest mortality occurring in cleavage and gastrula stage embryos exposed to 30 lg/l MeHg.…”
Section: Acute Toxicitymentioning
confidence: 98%
“…Sharp and Neff (1980) also found a reduction in hatching success in Fundulus at 10 lg HgCl 2 /l. Weis and Weis (1977) noted that 100 lg/l HgCl 2 killed all Fundulus embryos prior to the onset of gastrulation. While Samson and Shenker (2000) found that early zebrafish (Danio rerio) embryos were most susceptible to MeHg toxicity, with highest mortality occurring in cleavage and gastrula stage embryos exposed to 30 lg/l MeHg.…”
Section: Acute Toxicitymentioning
confidence: 98%
“…High concentrations of mercury have also been shown to affect other aspects of teleost reproduction. Developmental abnormalities have been observed in a variety of teleost species, including Oncorhynchus kisutch (53-120 µg Hg/l) (Devlin and Mottet 1992), Salvelinus fontinalis (0.93-2.9 µg Hg/l) (McKim et al 1976), and Fundulus heteroclitus (20-40 µg Hg/l) (Weis and Weis 1977). Kirubaragaran et al (1992) reported retardation of gamete maturation in C. batrachus (32-37 µg Hg/l), and Bano and Hasan (1990) and Wester and Canton (1992) described inhibition of oogenesis in Heteropneustes fossilis (148 µg Hg/l) and spermatogenesis in Poecilia reticulata (4.5-8.0 µg Hg/l), respectively.…”
Section: Fishmentioning
confidence: 99%
“…Most laboratory investigations into the effect of mercury on fish populations employ concentrations and methods of exposure that are not environmentally relevant. Studies designed to elucidate the influence of mercury on teleost reproduction, an important determinant of fish populations, have exposed fish primarily to water-borne mercury concentrations in the µg/l range (McKim et al 1976;Weis and Weis 1977;Snarski and Olson 1982;Joy 1988, 1992;Dey and Bhattacharya 1989;Bano and Hasan 1990;Dave and Xiu 1991;Devlin and Mottet 1992;Wester and Canton 1992). In contrast, mercury levels in natural waters of North America rarely exceed the ng/l range (Wiener and Spry 1995).…”
mentioning
confidence: 99%
“…Among the environmental pollutants producing these anomalies are alkaline pH in the Atlantic salmon, Salmo salar (34), cadmium in S. gairdneri (35), carbaryl in Fundulus heteroclitus (18), carbaryl, parathion and malathion in Oryzias latipes (36), mercury compounds in Fundulus heteroclitus (31,32), mercury in Oryzias latipes (37), lead in Brachydanio rerio (13), toluene in 0. latipes (38), toluene in Pimephales promelas (39), 2,4,5-T in 0. latipes (40), ethyl carbamate in Brachydanio rerio (41), and aflatoxin in 0. latipes (42). It is believed that the pericardial edema is a result of a fluid imbalance caused by the retarded circulation (17).…”
Section: Cardiac Malformationsmentioning
confidence: 99%
“…Flexures and stunting have been observed in Brachydanio rerio treated with ethyl carbamate (41), Pimephales promelas treated with toluene (39), Oryzias latipes treated with aflatoxin (42), Fundulus heteroclitus treated with mercury compounds (31,32), Oryzias latipes treated with methylmercury (47), F. heteroclitus treated with water-soluble fractions of oil (48), and S. gairdneri treated with cadmium (35). Stunting and bent axes have been produced in amphibian embryos by exposure to a variety of herbicides and fungicides (25,49), or to mercury (50).…”
Section: Skeletal Defectsmentioning
confidence: 99%